Surveys of post-operative pain management in a teaching hospital in Rwanda — 2013 and 2017. Issue 1 (1st January 2019) - McKay, William; Lee, Danyela; Masu, Adolphe; Thakore, Shefali; Tuyishime, Eugene; Niyitegeka, Joseph; Ruhato, Paulin; Twagirumugabe, Theogene; O'Brien, Jennifer
ABSTRACT: Background: Postoperative pain management (POPM) appeared to be weak in Rwanda. Aims: The aim of this study was to compare POPM measures in a teaching hospital between 2013 and 2017. Methods: A two-phase observational study in 2013 and 2017. was conducted. Participants were recruited prior to major surgery and followed for two postoperative days. A numerical rating scale (0–10) was administered to all participants in both years, and the International Pain Outcomes questionnaire was administered in 2017. Recruitment, consent, and data collection were performed in participants' preferred language. Results: One hundred adult participants undergoing major general, gynecologic, orthopedic, or urologic surgery were recruited in 2013 and 83 were recruited in 2017. Fourteen percent of participants in 2013 and 46% in 2017 scored their worst pain as severe (>6; P < 0.001). This was despite improved preoperative recognition of patients at high risk for severe postoperative pain (those with chronic pain or preoperative pain); 27% and 0% of these patients were not documented in 2013 and 2017, respectively ( P = 0.006). Other measures of improved planning included "any preoperative discussion of POPM" ( P < 0.001) and "discussion of POPM options" ( P = 0.002). Preemptive analgesia use increased (3% of participants in 2013 and 54% in 2017; P < 0.001). Incidence of participants having no postoperative analgesic at all decreased from 25% in 2013 to 5% in 2017 ( P < 0.001). Conclusions: Though severe postoperative pain incidence did not improve from 2013 to 2017, POPM improved by a number of measures. These changes may be attributed to pain research conducted there having raised awareness.